Effectiveness of alternative assessment tools used in EiS-SULAM projects for sustainable communities in engineering programme / Che Maznah Mat Isa ... [et al.] - Mat Isa, Che Maznah; Ab Rani, Nur Izzati; Kamaruddin, Mohd Khairul; Abdull Rahman, Siti Hamidah; Lokman, Nurul Fariha (2023)
Service-Learning Malaysia-University for Society (SULAM) approach integrates theory and practice to expose students to real-world community problems and develop their higher-order thinking skills (HOTs). However, there is a lack of research on alternative assessment tools used to evaluate SULAM projects in engineering programs. This study focuses on the assessment tools used for the Engineers in Society (EIS) course integrated with SULAM (EiS-SULAM) and their effectiveness. A questionnaire survey was administered to 462 civil engineering students who took the EiS-SULAM course during the October 2020, March 2021, and October 2021 semesters. Of the 462 students, 165 responded to the questionnaire, resulting in a response rate of 36%. The students' perspectives were triangulated with the direct attainment of the program outcomes for the course based on the assessments used. The results showed that all students met the 50% cut-off mark for the EiS-SULAM course, satisfying the EAC Standard 2020 criterion. The study highlights that the four assessment tools used in the EIS course are effective, but there is a room for improvement. The students suggested the need for financial support from the university, improvements to the assessment tools, facilities such as internet, conducive environment to enhance their learning experience, and additional support from lecturers/advisors highlighting the importance of quality guidance and mentorship for student success. The study's findings could help improve engineering assessment instruments to enhance the students' skill sets related to sustainable community. However, the use of purposive sampling may limit the generalizability of the results to other engineering programmes or institutions. The results suggest that the EIS-SULAM course is effective in developing students' HOTs and achieving essential skill sets for societal well-being. In conclusion, this study provides valuable insights into the effectiveness of assessment tools in SULAM projects for engineering programmes and its potential to develop the essential skill sets required for community and societal well-being. Future research could explore the effectiveness of SULAM in different engineering programmes and institutions using different sampling methods. In addition, promising avenue for future research is the integration of Artificial Intelligence (AI), such as ChatGPT, in the development of assessment prompts for engineering courses. This research could focus on creating AI-powered prompts aligned with course and program outcomes to enhance the efficiency and effectiveness of student evaluation.